ENGINEERING CALCULATIONS FILTERING THE SUSPENSION THROUGH ODNORODNUYUI DVUHSLOYNUYUZAGRUZKI - , В. Л. (Municipal economy of cities. Series: «Economy science», 2013)
An efficient approximate solution of problems filtering the slurry at a constant speed through a uniform and two-layer load with linear kinetics, mass transfer. The example shows their high accuracy.